Association between ankle-brachial systolic index, pulse oximetry gradient index and CT angiogram of lower limb among type 2 diabetic for detecting peripheral arterial disease - Talib, Norain (2017)
Background: Peripheral arterial disease (PAD) is a known macrovascular complication of type 2 diabetes. Most primary care clinic has no establish algorithm on how to screen patient with PAD. Hereby, we conducted a study among patient in tertiary hospital diabetic unit, by using simple useful, handy test and correlate the tests with diagnostic imaging to detect PAD in our local community in Kubang Kerian, Kelantan. Objective: To determine association between ankle-brachial systolic index, pulse oximetry and CTA lower limb for detecting peripheral arterial disease among Type 2 Diabetic patients. Methodology: Patients who attended Diabetic Specialist Clinic HUSM were eligible for the study. Adult patients with Type 2 DM has HbA1c more than 6.5% in 3 months were recruited. Symptoms of claudication were assessed using ECQ. The lower limb perfusion was evaluated by ABSI and PO gradient. Radiologically the perfusion was assessed using CTA LL as a gold standard. The severity of stenosis was categorized into <50% (minimal to mild stenosis) and ≥50%(moderate to severe stenosis). The site of stenosis (above and below knee) were also analysed. Results: A total of 22 limbs from 11 patients were analysed. A strong association between abnormal ABSI and LPO gradient (r = 0.818, p = <0.001) in this study was obtained. There is significant fair association between ABSI findings and history of lower limbclaudication (r = 0.378, p = 0.076) between patients. There was statistically significant association between present of stenosis and abnormal ABSI or PO gradient (p = 0.016). On further analysis, the odd of having abnormal ABSI or PO gradient value is 12 times higher in patient with moderate to severe stenosis than those with minimal to mild arterial PAD (ORc ,95% CI). In single logistic regression, the odd of having abnormal ABSI or PO gradient value is 8 times higher in patient with moderate to severe below knee arterialstenosis (≥ 50% stenosis) than those with minimal to mild (<50%) above and below knee PAD (p = 0.037). Conclusions: Patients who have severe below knee PAD has shown strong association with abnormal ABSI and PO. PO gradient has significant association with PAD as equal as ABSI and the result was confirmed by CTA LL study.